TINJAUAN PENETAPAN PERPU NOMOR 2 TAHUN 2022 TENTANG CIPTA KERJA DALAM PERSPEKTIF SOSIOLOGI HUKUM - AA Muhammad Insany Rachman; Evi dwi Hastri; Rusfandi Rusfandi (LPPM Universitas Nias Raya, 2023)
This study aims to find out about how the government views and the public's response regarding the government regulation in lieu of law job creation. This research is categorized as normative legal research through a juridical-normative approach, then by examining primary legal materials, namely regulations related to legal issues, then this research is focused on examining how legal sociology plays a role in finding solutions to existing problems. The results showed that the community still had time and effort to respond to the Perpu by actively participating in escorts before it became an Act, namely by demonstrations and requests for material test submissions.